If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(2x-1)=-57
We move all terms to the left:
3(2x-1)-(-57)=0
We add all the numbers together, and all the variables
3(2x-1)+57=0
We multiply parentheses
6x-3+57=0
We add all the numbers together, and all the variables
6x+54=0
We move all terms containing x to the left, all other terms to the right
6x=-54
x=-54/6
x=-9
| 4f–12=36 | | 2. 4f–12=36 | | x/6=x-1/2 | | 5x+4x=3x+12 | | 24=4(12−s) | | 6l−45=l | | 2x=−62x=−6 | | 22(2+w)=77 | | 4x*360=7x | | 12x³-4x=0 | | 4y-8=+12 | | 9^2×+3=27^x+5 | | –9−c=–7+7−10c | | 4x*x-9=-(2x+3)(x-2) | | 4x²-9=-(2x+3)(x-2) | | (U-4)x9=36 | | 2(4w+9)/5=-7 | | x²+x-1890=0 | | X²+x=1890 | | 7s-35=168 | | B=8×(4b+6) | | |x-1|+7=3x | | 7-5x=3x+11 | | 3(-9)–2g=2 | | 4.8x-9=-2 | | 3x-1,5=16.5 | | 1.5x-+3=-24 | | 131=1115a | | 5(12+3x)=165 | | 13^2x+2=2 | | 0.2/x=2.5 | | 5/18/b=14 |